é só pra multiplicar cruzado
![\frac{3x + 4}{x + 2} = \frac{3x - 1}{x} \frac{3x + 4}{x + 2} = \frac{3x - 1}{x}](https://tex.z-dn.net/?f=+%5Cfrac%7B3x+%2B+4%7D%7Bx+%2B+2%7D++%3D++%5Cfrac%7B3x+-+1%7D%7Bx%7D+)
Soluções para a tarefa
Respondido por
1
(3x + 4) ___(3x - 1)
------------- = ----------- ( só cruzar)
(x + 2)_____(x)
(x)(3x + 4) = (x + 2)(3x - 1)
3x² + 4x = 3x² - 1x + 6x - 2
3x² + 4x = 3x² + 5x - 2 veja
3x² + 4x - 3x² - 5x = - 2
3x² - 3x² + 4x - 5x = - 2
0 - 1x = - 2
- 1x = - 2
x = - 2/-2
x = + 2/1
x = 2 ( resposta)
Perguntas interessantes